ISOLATION AND PURIFICATION OF GLUCOSYLTRANSFERASE FROM MUTANS STREPTOCOCCUS SOBRINUS (SEROTYPE G) LOCAL ISOLATE (Iraqi Journal of Medical Sciences, 2016)
Background: Glucosyltransferase is an extracellular enzyme produced by mutans streptococci responsible for polymerizing the glucose moiety of sucrose to form glucan.Objective: Isolation and purification of glucosyltransferase from mutans Streptococcus sobrinus.Methods: The enzyme was purified from mutans Streptococcus sobrinus byultrafiltration , adsorption chromatography, ion-exchange by DEAE-cellulose and gel filtration by Sephacryl S-200.Results: Large scale production, concentration and purification of mutans streptococci (S.sobrinus) (serotype G) N10 glucosyltransferase (GTF) were done by ultrafiltration-method using an Amicone-filter P50,adsorption hromatography (hydroxyapatite beads), ion-exchange chromatography (DEAEcellulose column) and gel-filtration chromatography using (Sephacryl S-200)column. Three purified GTF enzymes (GTF-Ia,GTF-Ib, GTF-II) were detected with a specific activity of (31.60; 31.50 and 66.270) Unit/mg protein respectively and the fold of purification are (27.59; 27.92 and 58.75 respectively with yield of enzymes (14; 10.94 and 17.11 %) respectively.Conclusion:The purified enzyme with accepted yield may open new approaches for its using in oral passive immunization against dental caries in experimental animals by using hen egg yolk antibodies specific for cell associated GTF of mutans streptococci bacteria. Keywords: glucosyltransferase , Streptococcus sobrinus, purification, adsorption chromatography.
Keywords: glucosyltransferase; Streptococcus sobrinus; purification; adsorption chromatography